The letters of Jerome: asceticism, biblical exegesis, and the construction of Christian authority in late antiquity - Cain, Andrew (Oxford early Christian studies, 2009)
Introduction -- 'The voice of one calling in the desert' -- Epistularum ad diversos liber : structure and contents -- Hieronymus eremita : the textualized 'saint' -- Rhetoric and reproach -- An ascetic conversion story in letters -- Introducing ... Jerome -- A pope and his scholar -- Jerome on Damasus on Jerome : revisionist reminiscences --The great commission --The correspondence : 'Hebrew verity' and Ambrosiaster -- Claiming Marcella -- Ad Marcellam epistularum liber : structure and contents -- Hagiography, hermeneutics, Hebrew, and heretics -- Sealing a spiritual and scholarly legacy -- Expulsion from Rome -- Theological controversy -- The gathering storm : Blesilla's death -- The beginning of the end -- The 'disgrace of a false charge' -- Paula's seducer? -- The case against Jerome : trial and conviction -- Exile of a prophet -- The embattled ascetic saga -- Jerome's personal, theological, and ecclesiastical profiles -- Jerome's spiritual advice -- Legitimization -- The exegetical letters -- Remembering Fabiola, defending Hebrew verity -- From Bethlehem to the furthest reaches of Gaul -- Ep . 120 to Hedibia (Bordeaux) -- Ep . 121 to Algasia (Cahors?) -- Cultivated image